A Micropillar‐Assisted Versatile Strategy for Highly Sensitive and Efficient Triboelectric Energy Generation under In‐Plane Stimuli. Issue 2 (11th November 2019) - Chun, Sungwoo; Pang, Changhyun; Cho, Sung Beom
Abstract: For the application of portable and wearable devices, the development of energy harvesters sensitive to various types of local and subtle mechanical displacements is essential. One of the most abundant but difficult‐to‐harvest mechanical energies in everyday life is the in‐plane kinetic energy that arises from a rubbing motion. Here, an efficient method is proposed to generate electrical energy from tiny horizontal forces by laminating microstructures on a conventional triboelectric nanogenerator (TENG). The microhairy structures serve to induce contact friction between the two dielectric materials, driven by reversible mechanical bending when a contact rubbing pressure or noncontact airflow is applied in the horizontal direction. Compared to TENG devices without microstructures, the introduction of microstructures greatly enhances the energy harvesting in the same situation. In addition, the TENG device with micropillars can generate electrical output under tiny mechanical variations (<0.2 Pa) induced by a local deformation below individual micropillars. A high energy‐generation capability is demonstrated by rubbing textured samples on the micropillar‐structured TENG devices to induce horizontal contact friction. The devices can also efficiently harvest electrical energy from noncontact fluidic airflow. By assembling the microhairy structures on a conventional TENG, more complex and realistic mechanical motion can be harvested. Abstract : A novel and general method for efficient triboelectric energy generation is developed by assembling artificial micropillars on typical triboelectric nanogenerator devices. The hairy‐structured devices can efficiently harvest electrical energy from in‐plane stimuli such as contact rubbing pressure or noncontact airflow, which works even for extremely small mechanical variations (<0.2 Pa) efficiently.